Screening for Postpartum Depression and Anxiety in a Primary Pediatric Clinic - Amy Ladley; Zachary Burnett; Matthew Broom (Association of American Medical Colleges, 2016)
Abstract This presentation aims to increase awareness of postpartum depression, provide a successful model for postpartum depression screening in a pediatric primary care clinic, and provoke discussion of barriers to screening. The presentation will provide physicians in other pediatric primary care clinics who are interested in screening with a basis for implementing a postpartum depression screening program of their own that overcomes many of the current barriers to screening. This resource contains a PowerPoint presentation with small-group discussion questions, an instructor's guide that contains additional information to supplement the PowerPoint, and an example resource assessment questionnaire and housing resource sheet. This screening program has been successfully implemented at Danis Pediatric Center at Cardinal Glennon Children's Medical Center. The program was introduced and presented to physicians, nurses, and staff in order to educate them about the importance of postpartum depression and to promote buy-in to the screening program. The postpartum depression screening program was implemented in January 2012 and, as of July 2015, screens approximately 95% of new mothers for postpartum depression during their child's regularly scheduled well-child check. Additionally, the providers are audited every month and provided with their own personal screening rate for the past month as well as the screening rates of other providers in the clinic. This promotes personal responsibility and competition within the clinic in order to achieve the highest possible screening rate. The current screening rates broken down by provider range from 94% to 100%, indicating collective buy-in and participation in this screening program by all members of the team. The continuing success of this screening program indicates that staff understand the importance of screening for postpartum depression, have overcome many of the barriers to screening, and have collectively bought in to the screening program.